2017
DOI: 10.4236/jbm.2017.58009
|View full text |Cite
|
Sign up to set email alerts
|

Trivalent Chromium Promotes Healing of Experimental Colitis in Mice by Suppression of Inflammation and Oxidative Stress

Abstract: Ulcerative colitis (UC) has reactive oxygen species (ROS) and immunologic pathways implicated in its pathogenesis. The search for new therapeutic protocols in managing UC is tailored in suppressing or preventing these pathways. The influence of trivalent chromium (Cr 3+ ), an essential mineral on experimental colitis was investigated. Mice were grouped into 3; group 1 (control) received clean drinking water while groups 2 and 3 received 10 and 100 ppm Cr 3+ respectively for 12 weeks through drinking water. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Cr content in H. aspersa Müller foot tissue lyophilisate was ten times higher comparing to the content in dry matter of oysters edible parts [ 37 ]. In the study of Odukanmi et al, trivalent Cr improved colitis healing in mice by promotion of antioxidant activities, suppression of ROS and inflammation [ 60 ]. In turn, chronic administration of hexavalent Cr in high doses elicited alimentary cancers in mouse models [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cr content in H. aspersa Müller foot tissue lyophilisate was ten times higher comparing to the content in dry matter of oysters edible parts [ 37 ]. In the study of Odukanmi et al, trivalent Cr improved colitis healing in mice by promotion of antioxidant activities, suppression of ROS and inflammation [ 60 ]. In turn, chronic administration of hexavalent Cr in high doses elicited alimentary cancers in mouse models [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It not only increases insulin sensitivity [26,27] and improves lipid metabolism [28] but also reduces the oxidative stress [29], body weight, and body fat mass [30] in those patients. Several studies have been reported that chromium (III) increases the cellular antioxidant capacity in mice and rats [31,32]. Recently, it also has been shown that chromium could inhibit hepatic steatosis in rats given a high-fat diet [33].…”
Section: Introductionmentioning
confidence: 99%
“…This ferent in comparison to untreated RA rats (P ≤ 0.05), ## significantly different in comparison to untreated RA rats (P ≤ 0.001), @ significant difference between both treated groups (P ≤ 0.05), @@ significant difference between both treated groups (P ≤ 0.001) (Odukanmi et al 2017). Cr (III) also showed up-regulatory effects on other anti-inflammatory cytokines (Moradi et al 2019).…”
Section: Discussionmentioning
confidence: 84%
“…This study revealed that Cr (III) up-regulates FOXP3 expression which means subsequent remission of RA (Kanjana et al 2020 ) and this goes in line with the up-regulation of the anti-inflammatory cytokine IL 10 (Greenhill et al 2014 ) in Cr (III) treated RA group that was even exceeding that of prednisolone in this study. IL 10 increase after Cr (III) supplementation was shown in the study of Odukanmi O. et, al who used Cr (III) in induced inflammatory colitis (Odukanmi et al 2017 ). Cr (III) also showed up-regulatory effects on other anti-inflammatory cytokines (Moradi et al 2019 ).…”
Section: Discussionmentioning
confidence: 93%